The Analytical Capabilities of Electrochemical Sensors Based on Transition Metal Oxide Nanomaterials - Guzel Ziyatdinova; Liliya Gimadutdinova; Tatyana Antonova; Irina Grigoreva; Elvira Yakupova (Engineering Proceedings, 2023)
Voltammetric sensors based on CeO2, SnO2, CeO2·Fe2O3 nanoparticles (NPs) and MnO2 nanorods (NRs) were developed for the quantification of various organic substances. Surfactant media were applied as dispersive agents for metal oxide nanomaterials, providing a high stability of the dispersions after sonication and a decrease in the NPs’ size, as well as the preconcentration of the target analytes at the sensor surface due to the hydrophobic interactions between the surfactant and the analyte molecules. Natural phenolics (quercetin, rutin, gallic acid, taxifolin, eugenol, vanillin, and hesperidin), propyl gallate, α-lipoic acid, and synthetic food colorants (tartrazine, brilliant blue FCF, and sudan I) were studied as analytes. The effect of the nature and concentration of the surfactant on the target analyte response was evaluated. Cationic surfactants (cetylpyridinium (CPB) or cetyltriphenylphosphonium bromides (CTPPB)) showed the best effect for the majority of the analytes. Wide linear dynamic ranges and low detection limits were obtained and were improved vs. reported to date. The simultaneous quantification of tartrazine and brilliant blue FCF was achieved with a high selectivity. The practical applicability of the sensors was shown on the real samples and was validated by comparison to independent methods.